Efeitos da caminhada autosselecionada sobre marcadores bioquímico-metabólicos de mulheres adultas obesas - Garavelo, João Júlio (2012)
To evaluate the effects of 12 weeks of an exercise program involving self-seletd rhythim on biochemical and metabolic markers in obeseadult women. A total of 50 obese women who were randomly assigned into two groups, experimental group (CAS): 25 women, aged 47.8 ± 6.4 years and a control group (CON): 23 women, aged 47.8 ± 8.4 years. The experimental group was subjected to a walking program, being held three times a week with self-selected intensity for twelve weeks, while the control group did not do any type of physical exercise on a regular basis. We evaluated anthropometric, and biochemical analysis of blood counts at baseline and after twelve weeks in both groups. There was no significant difference for the data of body mass (CON = 89.9 ± 14.0 kg pre, post 90.5 ± 11.2 kg vs. 86.4 ± 10.1kg, CAS pre, after 82.7 ± 11 , 5 kg, p> 0.05) and BMI (CON = 35.7 ± 3.2 kg/m2 pre, post 36.0 ± 2.9 kg/m2 vs. 34.4 ± 2.9 pre CAS kg / m2, post 34.5 ± 3.4 kg/m2, p> 0.05). For the analysis of biochemical markers and complete blood count occurred the following modifications: total SSR group showed reductions (~ 16%) and triglyceride blood there was a reduction (~ 15%) between pre-and post-training for the CAS group (p <0.05), HDL cholesterol values showed increases (~ 17%) significant for the CAS group between pre and post-experimental (p <0.05) levels of blood glucose, insulin and HOMA-IR reduced (~ 10% ~ 16% and ~ 25%, respectively) significantly between pre-and post-training for the CAS group (p <0.05). Sedentary and obese women who underwent walking self-seletd were able to promote significant positive changes in triglycerides, HDL and VLDL, without changes in complete blood count. No significant changes occurred for both groups in markers of renal and hepatic function. Insulin resistance was the variable that was altered expressive, positively by modifying self-seletd walk without dietary intervention. Walking into a physiological rhythm itself as well as changes in metabolic and biochemical biomarkers in sedentary obeses women.